COMPARATIVE STUDY OF THE EFFECTIVENESS OF CERTAIN PREPARATIONS IN THE FORM OF OINTMENTS AND SOLUTIONS FOR STANDARD AND HOSPITAL STRAINS OF BACTERIA - Штанюк, Є.А.; Безугла, О.П.; Ляпунов, М.О.; Mynuhyn, V. (World of Medicine and Biology, 2015)
Introdaction. Treatment of infected wounds is one of the urgent problems of medicine. Leading among pathogens of inflammatory infections are staphylococci and gram-negative bacteria, mainly Pseudomonas aeruginosa and Escherichia coli. There is an increasing incidence of septic complications caused by hospital antibioticresistent strains. Particular danger is epidemic spreading and infection of wounds by Staphylococcus aureus MRSA. For topical treatment of infected wounds in the 1-st phase of wound healing is widely using of antibacterial ointments and solutions on hydrophilic bases, for example, with such antibiotics such as chloramphenicol and ofloxacin, as well as other active ingredients of antibacterial action: dioxydine, nitazol and streptocide (in combination ) and so on. These drugs have been developed and introduced into medical practice in another 70-90 years of the last century. Therefore, an important question is whether they are effective against major modern hospital strains of polyresistent bacteria. The purpose of the study. The election of promising active antibacterial substance for the development of ointments and solutions for local treatment of purulent wounds on a comparative study of antibacterial action of industrial and experimental samples of drugs against the standard strains of S. aureus, E. coli and P. aeruginosa and hospital polyresistent strains of these bacteria. Materials and Methods. We investigated Oflokain-Darnitsya ointment Nitacid-Darnitsya ointment, Dioxizol-Darnitsya solution, Levomekol ointment, ointment 5% Dioxidine and experimental samples of Dioxidine ointment 1.2% and Dioxizol solution with different concentrations dioxidine: 0.25% 0, 50%, 0.75%, 1.00%, 1.25% and 1.50% by agar diffusion method. Antibacterial activity was determined on standard strains of S. aureus ATCC 25923, E. coli ATCC 25922, P. aeruginosa ATCC 27853 and clinical polyresistant strains of S. aureus № 910, E. coli № 6, P. aeruginosa № 16. Results and discussion. All study drugs showed effective or highly effective antibacterial activity against standard strains of bacteria S. aureus ATCC 25923, E. coli ATCC 25922, P. aeruginosa ATCC 27853. All three hospital strains of bacteria in the previous studies wake resistant to ofloxacin, but strain of S. aureus № 910 was highly sensitive, strain of E. coli № 6 was sensitive, strain of P. aeruginosa № 16 was insensitive to Oflokain Darnitsya ointment. All three clinical strains of bacteria were sensitive to the Levomekol ointment and showed high sensitivity to drugs with dioxidine that had an advantage over other investigated ointments. Dioxidine revealed highly antibacterial effect on all 3 clinical studied strains (zone growth delay were more than 25 mm) at concentrations ranging from 1.0% to 1.5%. Сonclusions. Preparations with dioxidine showed highly effective antimicrobial action against antibiotic resistant clinical isolates of bacteria and had the advantage over other studied preparations, particularly with the ointments with ofloxacin and chloramphenicol. It is shown that for the manifestation of highly effective antimicrobial action against hospital strains of bacteria dioxidine should be included in the preparations at concentrations ranging from 1.0% to 1.5% for the topical treatment of wounds.